DESIGN, DEVELOPMENT AND EVALUATION OF NOVEL SUSTAINED RELEASE BI-LAYER TABLETS OF LORNOXICAM BASED ON THE COMBINATION OF HYDROPHILIC MATRIX FORMERS AND BASIC PH MODIFIERS. - NABIN KARNA (International Journal of Pharma and Bio Sciences, 2012)
This bi-layer matrix tablets were formulated to show quick onset of action as well as prolonged effect of drug in the body. Lornoxicam is weak acidic in nature, so its release from SR delivery systems is limited to the lower gastrointestinal tract which consequently leads to a delayed onset of its analgesic action. To provide complete drug release that starts in the stomach to rapidly alleviate the painful symptoms and continues in the intestine to maintain protracted analgesic effect, use basic pH modifiers like sodium bicarbonate & magnesium oxide to create basic micro-environmental pH inside &give a favorable acidic condition for tablets to release the drug. Different types and levels of hydrophilic matrixing agents, like HPMC K4 & HPMC K 15 were used to control the release of the drugs. The UV Spectroscopy, particle size and FTIR analysis of pure drug were performed. The tablets were prepared by wet granulation. In-Vitro drug release study was carried out for different formulations.